About Death and All its Images: Editorial - Vives-Ferrándiz Sánchez, Luis (Eikón / Imago, 2021)
Leader article of Eternal sadness; representations of death in visual culture from Antiquity to the present time. The aim of this monography is to study the representations of death in visual culture of different chronologies and places. To this aim, the monography brings together papers related to a variety of disciplines that analyse the relationships between images and death.